DOMESTIC WASTEWATER TREATMENT WITH MODIFIED ADDITION OF PUMICE AND PALM FIBERS-GRAVEL FILTER IN THREE CONCENTRIC SEPTIC PIPES (TRIPIKON-S) FOR APPLICATION IN SPECIFIC AREAS - Syakinah, Siti
One of the problems faced by slums is the low access to good sanitation. This is a challenge in improving and increasing access to sanitation by paying attention to the selection of appropriate, affordable, sustainable technology, and in accordance with the environment. One technology that can be applied to slums is Tripikon-S which consists of three (tri) concentric (pi) pipes (kon) septic (S), as one of the domestic wastewater treatment solutions for specific areas. Various modifications have been made to achieve the best efficiency. In this study, laboratory-scale testing was carried out on the Tripikon-S modification with the addition of pumice stones in the large pipe (third pipe) and a fiberglass-gravel filtration system in the Tripikon-S outlet pipe. Pumice stones are placed on the outermost 8-inch pipe as many as 45 pieces. The fiberglass-gravel filter is located at the outlet end of the reactor with a thickness of 10 cm each for fiberglass and 10 cm for gravel. Testing of this modified reactor is divided into batch and continuous processes. In the batch process, the waste variation used is black water waste with a COD load of 500 mg/L, 750 mg/L, and 1,000 mg/L which is run for 3 days. Then continued testing the performance of the reactor under continuous conditions with variations of black water waste (COD 750 mg/L) and mixed wastewater waste (300 mg/L) run with HRT 48 hours (2 days). Analysis of COD removal kinetics using first-order kinetics and bacterial growth was analyzed using Monod kinetics. To identify the microbial community on pumice, the 16 r-RNA sequencing method was used, and the Scanning Electron Microscope method was used to look at the morphology of the attached media, namely pumice. The removal in the batch process resulted in ?max 0.0168/hour, Ks 421.023 mg/L COD/hour, and yield 1.829. The substrate degradation rate (k) at concentrations of 500, 750, and 1,000 mg/L was found to be 0.0612/hr, 0.0518/hr, and 0.0489/hr, respectively. The black water effluent removal showed that the modified reactor was better than the control reactor. The addition of fiber-gravel filters in the continuous process did not provide an increase in efficiency in the COD parameter of 17.75% and TSS of 24.86%. The test results (p = 0.223) show that there is no significant difference in the modified Tripikon-S in the treatment of black water waste compared to mixed water waste.